Rectal Pocket Syndrome: A Symptomatic Rectal Pseudodiverticula as a Long-Term Complication of Failed Purse-String Suture During Stapled Hemorrhoidopexy - Cristopher Varela (World Journal of Colorectal Surgery)
Short- and long-term complications of stapled hemorrhoidopexy have been extensively discussed during the popularization of the technique, with set complications remarkably decreasing with the progress of learning curves and improvements in the technique. We describe the management of a 58-year-old woman with a history of stapled hemorrhoidopexy who presented with proctalgia and recurrent tenesmus 12 months after the intervention. A 4-cm diverticulum in the lower rectum with fecal material inside was evidenced without a fistula. A transanal diverticulectomy was performed with primary repair of the rectal wall, with the postoperative disappearance of the symptoms. Iatrogenic rectal pseudodiverticul is an infrequent complication due to areas of focal weakness along the rectal wall after failing to complete resection of the mucosa at the circumference of the anastomosis or ineffective stapling of the entire circumference.